Morphological Events during the Cell Cycle of Leishmania major - Audrey Ambit; Kerry Woods; Benjamin Cull; Graham H. Coombs; Jeremy C. Mottram (2011)
ABSTRACT The morphological events involved in the Leishmania major promastigote cell cycle have been investigated in order to provide a detailed description of the chronological processes by which the parasite replicates its set of single-copy organelles and generates a daughter cell. Immunofluorescence labeling of β-tubulin was used to follow the dynamics of the subcellular cytoskeleton and to monitor the division of the nucleus via visualization of the mitotic spindle, while RAB11 was found to be a useful marker to track flagellar pocket division and to follow mitochondrial DNA (kinetoplast) segregation. Classification and quantification of these morphological events were used to determine the durations of phases of the cell cycle. Our results demonstrate that in L. major promastigotes, the extrusion of the daughter flagellum precedes the onset of mitosis, which in turn ends after kinetoplast segregation, and that significant remodelling of cell shape accompanies mitosis and cytokinesis. These findings contribute to a more complete foundation for future studies of cell cycle control in Leishmania .